Manajemen arus kas dalam menjaga stabilitas keuangan perusahaan - naqibuddin006, Naqibuddin (Maliki Interdisciplinary Journal, 2026)
Cash flow management is a critical component in maintaining a company’s financial stability, particularly amid increasingly dynamic business environments. Effective cash flow management enables firms to meet short-term obligations, sustain smooth operational activities, and reduce the risk of liquidity shortages. Managing cash flow involves not only recording inflows and outflows, but also planning, controlling, and analyzing cash movement patterns to ensure balance between operational needs and long-term growth strategies. In a highly competitive market, companies must be able to accurately forecast cash requirements, optimize the cash cycle, and minimize mismatches between the timing of receipts and expenditures. This abstract highlights the importance of systematic cash flow management as a means of preserving financial stability, while also illustrating how structured cash planning and continuous monitoring can enhance a company’s efficiency and financial resilience.